DIVERSIFIKASI PRODUK OLAHAN IKAN UNTUK MENCEGAH KEJADIAN STUNTING PADA ANAK - Rifka Putri Andayani; Lenni Sastra; Putri Nelly Syofiah; Refki Riyantori; Dika Dwi Muharamsyah; Susi Lidiyawati; Rosiana Wulandari; Aulia Wulandari; Putri Mayanda Sutami; Mahkfira Putria Roza (JURNAL ABDI MERCUSUAR, 2023)
Background: The results of the community's livelihood as fishermen in the Bestari Fisherman's Village are caught fish such as tuna, tuna and skipjack. This fish is caught by fishermen using a chart. People are not fully aware of the benefits of consuming fish. Processed fish products can be used as a source of protein for pregnant women and can prevent stunting in children. Pregnant women can consume fish so start preparing for the first 1,000 days of life. Method: This community service activity begins with the data collection stage for partners and the results of observations, the preparation stage, the activity implementation stage by conducting training and knowledge transfer and ending with monitoring and evaluation. The method used in this community service is to provide knowledge transfer related to the diversification of processed fish products in the form of healthy snacks for school-age children to prevent stunting in children as well as provide entrepreneurship training and technology-based online product marketing done at home. Result: The basic ingredients of fish are very easy to obtain by the local community. The results of diversification of processed fish into healthy snacks can be produced by partners and partners can disseminate processed fish products through online media sales.